2014
DOI: 10.1242/jeb.104463
|View full text |Cite
|
Sign up to set email alerts
|

Learning to cope with degraded sounds: Female zebra finches can improve their expertise at discriminating between male voices at long distance

Abstract: Reliable transmission of acoustic information about individual identity is of critical importance for pair bond maintenance in numerous monogamous songbirds. However, information transfer can be impaired by environmental constraints such as external noise or propagation-induced degradation. Birds have been shown to use several adaptive strategies to deal with difficult signal transmission contexts. Specifically, a number of studies have suggested that vocal plasticity at the emitter's level allows birds to cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 41 publications
(49 reference statements)
0
25
0
Order By: Relevance
“…The sound level of the experimental signals, measured at a distance of 1 m from the loud speaker (Sound Meter, Model HD600, Extech Instruments, U.S.A), was adjusted to a peak value between 50.03 dB ± 0.87 dB (mean ± SD; minimum for the lowest call type, the tet) and 74.05 dB ± 1.15 dB (corresponding to the loudest call type, the distance call reflecting a typical level of a natural distance call) 39 , and was constant for all three familiarity levels of each call type.…”
Section: Methodsmentioning
confidence: 99%
“…The sound level of the experimental signals, measured at a distance of 1 m from the loud speaker (Sound Meter, Model HD600, Extech Instruments, U.S.A), was adjusted to a peak value between 50.03 dB ± 0.87 dB (mean ± SD; minimum for the lowest call type, the tet) and 74.05 dB ± 1.15 dB (corresponding to the loudest call type, the distance call reflecting a typical level of a natural distance call) 39 , and was constant for all three familiarity levels of each call type.…”
Section: Methodsmentioning
confidence: 99%
“…Although birds (Klump, 1996; Mathevon et al, 2008; Mouterde et al, 2014a) as well as many other animals (e.g., Mercado and Frazer, 1999) excel at recognizing the information embedded in communication signals degraded by propagation, the neural mechanisms mediating this task remained unexplored. We found neurons in the avian auditory forebrain displaying high discrimination for the identity of unfamiliar vocalizing birds, with remarkable invariance to the sound degradation induced by long-range propagation through the natural environment.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2007) have shown that behavioral performance for song discrimination is correlated with the performance of the most discriminating higher-level single neurons, which activity might potentially be reflecting the computations performed by the entire network. Using behavioral tests, we had previously found that female zebra finches were able to discriminate between the degraded calls of male zebra finches at up to 128 m without training and up to 256 m with training (Mouterde et al, 2014a). Here we found that single neurons could discriminate among unfamiliar individuals with calls that were degraded up to 256 m. Thus, there is an approximate match between single neuron performance and behavioral performance, with single neurons even outperforming behavioral tests in the sense that recognition at the longest propagation distance in behavioral testing was only achieved after repeated training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that zebra finches (Taeniopygia guttata) can learn to correctly discriminate among songs that have been degraded by distance (Mouterde et al, 2014).…”
Section: Familiarity With Noisementioning
confidence: 99%